ANALISIS MODAL SOSIAL DALAM TATA KELOLA AIR DI DESA BANYUURIP, SRAGEN, JAWA TENGAH - Ramawati, Triana; Zuber, Ahmad; Apolinaris Suryadinata, Theofilus; Dian Akbar, Rezza; Arif Mundayat, Aris; AyuHandayani, Fitri (Bajang Institute, 2025)
This study is a case study on the shift in water management patterns in Banyuurip Village, Sragen, Central Java, from traditional community-based systems to modern schemes such as Community-Based Water Supply and Sanitation (PAM Simas) and Rainwater Harvesting Infrastructure (IPAH). Using a qualitative case study approach, data were collected through in-depth interviews with 15 informants, participatory observation in three representative hamlets, and document analysis from August to October 2024. Findings indicate that while the shift improved water access from 45% to 87% of households (2018-2024), it also fostered dependency on external aid (78% of respondents), weakened collective participation in communal work (declined by 62%), and triggered social tensions over unequal distribution between highland and lowland areas. Analysis based on Bourdieu's (1986) concept of social capital and Ostrom's (1990) principles of commons governance reveals that water modernization without strengthening local institutions risks eroding the social foundation of sustainability. Comparison with similar studies in Nepal (Prasai et al., 2021), Ethiopia (Whaley & Cleaver, 2017), and Indonesia (Kooy & Bakker, 2022) demonstrates a universal pattern: technical water management without substantive participation results in social exclusion and social capital erosion. The study underscores the importance of integrating traditional values and community autonomy in rural water resource governance policies through hybrid institutional designs that combine modern efficiency with local legitimacy